Concurrent Bartonella henselae infection in a dog with panniculitis and owner with ulcerated nodular skin lesions. Issue 1 (8th October 2014) - Rossi, Michael A.; Balakrishnan, Nandhakumar; Linder, Keith E.; Messa, Jacqueline B.; Breitschwerdt, Edward B.
<x xml:space="preserve">Abstract</x> Background Bartonella henselae, a Gram‐negative, zoonotic Alphaproteobacteria that infects erythrocytes, endothelial cells and dendritic cells, has previously been implicated as a cause of panniculitis in dogs and a human. Animal and owner An 8‐year‐old, spayed female Labrador retriever and its 78‐year‐old male owner living in the same household. Methods and results When preliminary and advanced testing failed to identify the cause of near‐simultaneous‐onset dermatological lesions, Bartonella serology, Bartonella Alphaproteobacteria growth medium (BAPGM) enrichment blood culture/PCR and immunohistochemistry were used to test specimens from the dog and owner. Bartonella henselae, genotype San Antonio 2 DNA was amplified and sequenced from the man's BAPGM enrichment blood culture and the dog's panniculitis lesion. The bacterium was visualized by immunohistochemistry in the dog's panniculitis lesion; however, neither the dog nor the owner was B. henselae seroreactive. Antibiotic therapy elicited dermatological improvement in both dog and owner. Conclusions and clinical importance Bartonella henselae is an emerging zoonotic pathogen that induces granulomatous inflammatory lesions in various tissues of animals, including humans. We conclude that this bacterium had a contributory or causative role in the development of the dermatological lesions in the dog and owner.